Contemporary theories of liberalism : public reason as a post-Enlightenment project - Gaus, Gerald F. (Sage politics texts., 2003)
In this text, Gerald F. Gaus provides students with a comprehensive overview of the key tenets of liberalism developed through Hobbes, Locke, Kant and Rawls to present day theories and debates.